(untitled) (Journal of the College of Education for Women, 2023)
This research focuses on the contemporary geostrategic transformations that afflicted the countries of the Middle East, with a focus on the countries of the Arab East, after the collapse of the system of international relations, and the emergence of the unipolar system led by the United States of America. After the events of September 11 and the events that followed, especially the occupation of Iraq in 2003, the study area witnessed a group of geopolitical variables and the emergence of dangerous phenomena that threatened the state structure in the countries of the Middle East; the most notably are the phenomenon of terrorism, cross-border armed groups, sectarian polarization, the phenomenon of migration and the internal and the external displacement and the serious consequences that resulted from it, such as demographic change and the emergence of a failed state, which has become a threat to national and regional security in the region.One of the results of this security vacuum was the rise of active regional powers on the scene to fill the geopolitical vacuum, the change in the equation of the Arab-Israeli conflict, and the emergence of plans aimed at redrawing the political map of the countries of the region based on ethnic and sectarian division.